Dampak Pelaksanaanpredatory Pricing oleh Pedagang Seafood Mentah Perspektif Teori Sadd Dzari’ah Muhamad Abu Zahrah (Studi Kasus Pasar Pagi Kecamatan Medan Helvetia Kota Medan) - Fikri Hidayatullah, Muhammada Bimo; Zahara, Fatimah (Fakultas Syariah INSURI Ponorogo, 2023)
The perpetrators of predatory pricing by raw seafood traders at Pasar Pagi, Medan Helvetia District, are activities where traders sell products at prices below the cost of producing an item. With the first objective of predatory pricing is to get rid of opposing traders or competitors from the same market. However, after the trader succeeds in driving other business actors out of the market, then the trader raises the price again and maximizes the profits he gets. The purpose of this study was to determine the impact of predatory pricing on the morning market in Medan from the perspective of Muhammad Abu Zahrah. This study uses a qualitative approach to parse and explain the problem. This research is a field research (field research) with the type of normative-empirical research, in which the author conducts research based on applicable regulations with practices that are mostly carried out in society, where these practices are not in accordance with the applicable provisions as they should. The results of this study indicate that raw seafood traders as predatory pricing actors damage the price mechanism at the morning market in the Medan Helvetia sub-district which has been formed based on the sales environment in the market. The act of predatory pricing which is understood as being understood can provide an excuse for other traders which according to Muhammad Abu Zahra can cause something that causes damage or something that is prohibited. In this case, predatory pricing actors clearly provide an entry point for fraud against other seafood traders and this is not justified in Islamic law.